RELATIONSHIP MARKETING IN INTERNATIONAL FOCAL FIRMS: A STRATEGIC PERSPECTIVE ON SUSTAINABILITY - Bettani, Giovanni (My University, 2023)
ABSTRACT : In the intricate landscape of 21st-century business, this study addresses the challenges facing companies, particularly international focal firms, in meeting stakeholders' sustainability expectations. Requiring astute strategic decision-making, the focus is on the interplay between sustainability and Relationship Marketing (RM) theory in contemporary business networks. Current literature lacks a thorough exploration of the sustainability-marketing relationship, especially in the internationalization context, highlighting a critical research gap. Identifying this gap, the research underscores the need for a cohesive theoretical framework to comprehend how companies navigate relationships through sustainability. Thus, the study aims to construct a robust RM framework, synthesizing theories and identifying success factors. The Research Question is: “How can sustainability contribute to effective implementation of focal firms’ Relationship Marketing strategies?”. Sub-questions delve into internal operations, stakeholder engagement, and internationalization, forming the foundation for model development through data analysis and literature review. Using a qualitative design, three distinct case studies undergo analysis through semi-structured interviews with marketing and sustainability executives of international focal firms. Contributing to RM and sustainability theory, the study identifies ten forms of relational exchange, emphasizing shared values like sustainability as catalysts for active engagement. In the context of the Resource-Advantage view of competition, it explores the significance of idiosyncratic competence resources. Comparative analysis reveals three key competences: intra-firm sustainability competence, interfirm sustainability competence, and international sustainability competence—forming Sustainability Factors for meaningful global relational exchanges. Concluding, the research not only fills a critical research gap by establishing a foundation for exploring the intricate relationship between sustainability and Relationship Marketing but also provides insights for focal firms’ executives navigating diverse business contexts, while suggesting avenues for further research.
Keywords: relationship marketing; sustainable development; internationalisation; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business